2022
DOI: 10.1002/jcc.26836
|View full text |Cite
|
Sign up to set email alerts
|

Influence of conventional hydrogen bonds in the intercalation of phenanthroline derivatives with DNA: The important role of the sugar and phosphate backbone

Abstract: The influence of hydrogen bonds in model intercalated systems between guanine‐cytosine and adenine‐thymine DNA base pairs (bps) was analyzed with the popular intercalator 1,10‐phenanthroline (phen) and derivatives obtained by substitution with OH and NH2 groups in positions 4 and 7. Semiempirical and Density Functional Theory (DFT) methods were used both including dispersion effects: PM6‐DH2, M06‐2X and B3LYP‐D3 along with the recently developed near linear‐scaling coupled cluster method DLPNO‐CCSD(T) for be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
(308 reference statements)
0
4
0
Order By: Relevance
“…EDA serves as a powerful tool for scrutinizing the intricacies of bonding within both organic and inorganic compounds [60] . The results give the total binding energies (E int ), which equal the summation of three essential contributions, the orbital interaction E orb the electrostatic interaction (E elstat ), the repulsive exchange (Pauli) interaction E Pauli .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EDA serves as a powerful tool for scrutinizing the intricacies of bonding within both organic and inorganic compounds [60] . The results give the total binding energies (E int ), which equal the summation of three essential contributions, the orbital interaction E orb the electrostatic interaction (E elstat ), the repulsive exchange (Pauli) interaction E Pauli .…”
Section: Resultsmentioning
confidence: 99%
“…Repulsive exchange (Pauli) energy (ΔE Pauli ), orbital (covalent) energy (ΔE orb ), electrostatic energy (ΔE elect ), and dispersion energy (ΔE dis ). [35,36] The energies of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of molecules were calculated. Quantum chemical parameters of molecules reactivity: HOMO-LUMO energy gap, chemical hard-ness (η = (E LUMO À E HOMO )/2), [37] electronic chemical potential (μ = (E HOMO + E LUMO )/2), [29,38] global softness (S = 1/η) and electrophilicity index (ω = μ2/2η) [39,40] parameters were calculated for two molecules.…”
Section: Quantum Theory Of Atoms In Moleculesmentioning
confidence: 99%
“…In general, chemotherapy drugs are categorized as either groove binders or intercalators of DNA, which can result in changes in the parameters of the duplex structure, leading to therapeutic effects. 14 Previous studies have shown that flat molecules interacting from the minor groove side eject the mismatched DNA bases and bind through π-stacking. 15 In the intercalation mode, small molecules are included between the two base pairs of DNA, which are not in direct bonding.…”
Section: Introductionmentioning
confidence: 99%
“…These earlier studies provide utilitarian information about the interaction of CLQ with DNA; however, the molecular level picture about the DNA-drug binding such as the importance of the chemical nature and arrangement of nucleobases of DNA as well as the particular functional group of CLQ responsible for the interaction is almost lacking. The groove as well as intercalator mode of the binding of different chemical molecules with DNA has been studied earlier and has been correlated with the toxicity effect of molecules on DNA. It is known that the sequence of DNA controls many important biological processes such as replication and transcription, which can play an important role in the action of CLQ . Hence, it is essential to acquire the molecular level picture related to the role of the nucleobases as well as the functional group responsible for the action of CLQ to enhance the understanding of its action.…”
Section: Introductionmentioning
confidence: 99%